ORAL HEALTH AND DENTAL CARIES - Sura I.A.Jabuk; Anmar M. K. Al-Maamori; Rasha Kadhim Mahdi,; Shaymaa O. H. Al-Mamoori; Rafla'a S.H. Hussien, Noor M. Naji (Scholar Express Journals, 2022)
Dental disease is widespread among various groups, as tooth decay ranks second after the common cold, as it is widespread and as soon as the child reaches the age of five. Among the most important causes of tooth decay are carbohydrates, bacteria, susceptibility to caries, and the time factor, it divides tooth decay into the type of chronic caries and acute decay. The type of bacteria associated with decay is Staphylococcus Spp. Streptococcus pyogenes, Bacillus cereus, Escherichia coli and Proteus Spp.
Keywords: Tooth decay; Gingivitis; Oral disease,; Toothpaste